Classifying Occupational Hazards: Narratives of Danger, Precariousness, and Safety in Indian Mines, 1895–1970 - Nite, Dhiraj Kumar (International review of social history, 2025)
This article suggests that classification exercises were the quintessential modality for both the narrative and labour–management relations of occupational health and safety in Indian mines for the period 1895–1970. The extant literature has underestimated the cause-and-effect relationship that such classification practices had, including punitive safety regulation clauses, compensation clauses, the public image of firms, forms of knowledge, and stakeholder bargaining. The narrative of work hazards fundamentally forged casualty classification patterns. The ascertainment techniques applied to casualty, perceptions of occupational risk, and the politics of restitution shaped the narratives and defined patterns of casualty classification. Management devised various ways to present a decent picture of mining through casualty statistics. Later, critiques of this business practice exposed statistical discrepancies and flaws in the classification system, challenging the built-in business-blindness. From the late 1920s, the informed, organized mineworkers articulated their experiences of workplace risk; they confronted the managerial discourse of “unavoidable” work hazards and mineworkers’ liability for casualty. The mineworkers’ publicists and the government of the Republic of India took an interest in research on occupational health and safety and its regulation. They aimed at industrial efficiency and national reconstruction by creating a healthy, contented, and experienced workforce. All this steered the classification exercises of industrialists and public authorities towards favourable changes. The twin forces of capital and working people converged on the restitution measures articulated within the utilitarian paradigm. The latter, ironically, contributed to valorizing the narrative of risk and sacrifice in the lives of mineworkers.